Impact of Educational Intervention on HPV Vaccine Interest in Preclinical Medical Students - Yuliana; Chryzia Jacqueline Natividad, Rachel; Lilis; Hadiyanto; Riani, Mutiara (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objectives: To assess the role of education on HPV vaccination interest among preclinical medical students at School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia. Methods: This was a descriptive analytic study with cross-sectional method. The respondents of this study were 104 of preclinical medical students, School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, based on proportional sampling method. Data were obtained in November 2023 using questionnaires tool. The collected data were then statistically analyzed with univariate and bivariate analysis. Results: There was an increase that statistically significant in knowledge and HPV vaccination interest after educational intervention. And there was an association between education and HPV vaccination interest (p=0.000). Conclusion: There is a role of education on HPV vaccination interest among preclinical medical students at School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia.